High Tidal Volume Induces Mitochondria Damage and Releases Mitochondrial DNA to Aggravate the Ventilator-Induced Lung Injury - Lin, Jin-Yuan; Jing, Ren; Lin, Fei; Ge, Wan-yun; Dai, Hui-jun; Pan, Linghui (Frontiers in Immunology, 2018)
Objective: This study aimed to determine whether high tidal volume (HTV) induce mitochondria damage and mitophagy, contributing to the release of mitochondrial DNA (mtDNA). Another aim of the present study was to investigate the role and mechanism of mtDNA in VILI in rats. Methods: Rats were tracheotomized and allowed to breathe spontaneously or mechanically ventilated for 4 hours. After that, lung injury was assessed. Inhibition of Toll like receptor 9 (TLR9), named ODN2088, was used to determine the involvement of TLR9/ myeloid differentiation factor 88 (MyD88)/ nuclear factor-κB (NF-κB) signaling pathway in ventilator-induced lung injury (VILI). The mitochondrial damage and release of mtDNA were assessed. Pharmacological inhibition of mtDNA (chloroquine) was used to determine whether mtDNA trigger inﬂammation via TLR9 in VILI. EDU-labeled mtDNA deriving from mitophagy was assessed by immunofluorescence. The role of mitophagy in VILI was shown by administration of antimycin A and cyclosporine A. Main Results: Rats subjected to HTV showed more severe pulmonary edema and inflammation than the other rats. The decreased expression of TLR9, MyD88 and NF-κB were observed following the use of ODN2088. Mechanical ventilation (MV) with HTV damaged mitochondria which resulted in dysfunctional ATP synthesis, accumulation of reactive oxygen species and loss of mitochondrial membrane potential. Moreover, the results of distribution of fluorescence in rats upon HTV stimulation indicated that mtDNA cleavage was associated with mitophagy. The expression levels of mitophagy related genes (LC3B-II/LC3B-I, PINK1, Parkin and Mfn1) in animals ventilated with HTV were significantly up-regulated. Administration of antimycin A aggregated the histological changes and inflammation after mechanical ventilation, but these effects were attenuated when administered in the presence of cyclosporine A. Conclusions: Mechanical ventilation with HTV induces mitochondrial damage and mitophagy, contributing to the release of mtDNA, which may be induced VILI in rat via TLR9/MyD88/NF-κB signaling pathway.